Formulation optimization and antioxidant test for Self-nano emulsifying drug delivery system of soursop leaves (Annona muricata L.) chloroform extract using candlenut oil as oil phase - Anif Nur Artanti; Anggraini Febriyanty; Fea Prihapsara; Dian Eka Ermawati (Pharmaciana, 2021)
Soursop leaves (Annona muricata L.) chloroform extract has an anticancer agent that can be developed for traditional medicine preparation, even though the extract's solubility is low in the water. This study aims to generate new soursop leaves chloroform extract in the Self-Nano Emulsifying Drug Delivery System (SNEDDS). The expected result is that the solubility increases so that the drug delivery system is more effective. The extraction process of soursop leaves uses the percolation method with chloroform as a solvent. It used tween 80 and cremophore E.L. as surfactant, propylene glycol as a cosurfactant, and candlenut oil as a carrier, to make the SNEDDS formulation. Then performed a comparison between the optimal parameters for the physical properties of the SNEDDS formulation with the predictive Simplex Lattice Design (SLD) formulation with the students' t-test statistical analysis [p> 0.05]. Then carried out several tests such as loading dosage extractability, accelerated stability test, particle size, and zeta potential. Furthermore, the antioxidant test was carried out using the DPPH reagent. The optimum composition of candlenut oil, propylene glycol, a mixture of tween 80, and cremophor E.L. based on SLD is 12%: 22%: 66%, respectively. The SNEDDS optimum formulation for chloroform extract of soursop leaves produces a stable nanoemulsion, homogenous. It has a transmittance value of 90.58% Â± 0.151, emulsification time of 59.44 Â± 1.763 seconds, and a value of separation phase 1. The physical formulation test results showed no significant difference between observations with predictive design expert software. SNEDDS can produce 25.0 mg of soursop chloroform extract with particle size 411.4 nm, polydispersion index 0.482, and zeta potential 34.2 mV. IC50 value in 36.28 ppm indicated the antioxidant potential of the SNEDDS formulation for chloroform extract of soursop leaves is high.